A novel nanosphere-in-nanotube iron phosphide Li-ion battery anode displaying a long cycle life, recoverable rate-performance, and temperature tolerance. Issue 37 (13th September 2021) - Liu, Jinyun; Zhou, Ting; Wang, Yan; Han, Tianli; Hu, Chaoquan; Zhang, Huigang
Abstract : A novel nanosphere-confined one-dimensional yolk–shell anode is developed for Li-ion batteries. Abstract : Currently, non-ideal anodes restricts the development of long-term stable Li-ion batteries. Several currently available high-capacity anode candidates are suffering from a large volumetric change during charge and discharge and non-stable solid interphase formation. Here, we develop a novel nanosphere-confined one-dimensional yolk–shell anode taking iron phosphide (FeP) as a demonstrating case study. Multiple FeP nanospheres are encapsulated inside an FeP nanotube through a magnetic field-assisted and templated approach, forming a nanosphere-in-nanotube yolk–shell (NNYS) structure. After long-term 1000 cycles at 2 A g −1, the NNYS FeP anode shows a good capacity of 560 mA h g −1, and a coulombic efficiency of 99.8%. A recoverable rate-performance is also obtained after three rounds of tests. Furthermore, the capacities and coulombic efficiency remain stable at temperatures of −10 °C and 45 °C, respectively, indicating good potential for use under different conditions.